Проблеми практичного застосування системи окремих криміналістичних методик - Щур, Б.; Schoor, В. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті на підставі узагальнення поглядів вчених-криміналістів щодо проблеми розробки та інтеграції окремих криміналістичних методик, автором запропоноване бачення щодо порядку реєстрації та атестації окремої криміналістичної методики та порядок ведення реєстру. Запропонований порядок передбачається ведення у практичне застосування через нормативне визначення у підзаконних актах. In the article summarizes by the author the views of the forensic scientists regarding the problems of development and integration of forensic techniques; outlined the concept of relative order state registration and certification of special forensic methods and procedure for maintaining the registry. The proposed mechanism should promote generalization and systematization of certain forensic methods, quality control of their development. If a separate forensic technique was registered, its developer must obtain copyright certificate under applicable laws of Ukraine. Establishing a uniform procedure of certification and registration of individual forensic techniques, in addition, will be the basis for the development of new separate forensic techniques if needed and quality of their approbation.
Problems of Practical Application of the System of Special Criminalistical Methods
Keywords: окрема криміналістична методика; державна реєстрація; реєстр; атестація окремих криміналістичних методик; special criminalistical method; state registration; state attestation of separate criminalistical methods; criminalistics